Kajian Tingkat Kesejahteraan Pelaku Ekonomi Kreatif Di Kelurahan Pahoman Kota Bandar Lampung - Rahman, Yudha; Kurnianingsih, Nela Agustin; Maharani, Annisa; Falyajaya, Fatthah Ikhwan (Universitas Pahlawan Tuanku Tambusai, 2025)
Pahoman Village in the Enggal District of Bandr Lampung City is designated as a commercial and service area. Economic activities in this village drive local entrepreneurs to innovate and develop their products, often incorporating creative elements like social media marketing. This engagement in creative economic activities reveals the village's significant creative economic potential. The study aims to assess the welfare of creative economy actors in Pahoman Village. Using a mixed-method approach, the research identifies types of creative economic activities and scores to evaluate welfare levels. Findings show that most creative economy actors in Pahoman Village enjoy high welfare levels. However, it is recommended that government-led creative economic training be implemented to further enhance the capacity of these actors in Enggal District, Bandar Lampung City.